Pengaruh Model Pembelajaran Inkuiri Terbimbing terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Peserta Didik Kelas X MIA SMA Muhammadiyah Luhu - Waleulu, Amalia; Muharram, Muharram; Sugiarti, Sugiarti (Program Pasca Sarjana UNM, 2023)
This study is quasi experimental research with pretest-posttest control group design, which aims at examining the influence of guided inquiry learning model on critical thinking ability and chemistry learning autcomes of students on chemistry bond learning material. The population and the sampel of the study were all of students of grade X MIA at SMA Muhammadiyah Luhu. Sampel were chosen randomly and obtained grade X MIA 1as the experiment class and grade X MIA 2 as the control group. Data ceobtained were analyzed descriptively and inferentially. The ruselt of descriptive analysis obtained the mean score of critical thinking ability and learning outcome in experiment class by 79.85 and the control class 57.89, whit each of standard of deviation 11.77 and 12.29. The mean percentage of critical thinking ability indicator in experiment class is 83.91 in high category and in control class is 49.63 in moderate category. The result of hypothesis test with t-test at the level of significance α = 0.005 obtained tcount 4.48 > ttabel 2.20 and significance (0.001 < 0.05) indicated that the hypothesis is accepted. The conclusion of the study is there influence of guided inquiry learning model on the critical thinking ability and learning outcomes of grade X MIA at SMA Muhammadiyah Luhu on Chimistry Bond learning material.